Flexible Work Arrangements Availability and their Relationship with Work- Family- Conflict: The Moderating Effect of Employment Nature and Job Status - Mizanur Rahman, Mohammad; Binti Abdul, Mohani; Azman Ali, Noor; Jamal Uddin, Mohammad; Saidur Rahman, Mohammad (International Journal of Engineering and Technology, 2019)
The present study has explored the moderating effects of employment nature and job status on the relation between Flexible Work Arrangements (FWAs) and Work-Family-Conflict (WFC). Cross-sectional survey research design has been used and a structured self-administered survey questionnaire used to collect data from 330 employees working on private and public organizations in Bangladesh. Different statistical measures such as descriptive statistics, zero order correlation, Ordinary Least Square (OLS) multiple regression analysis, interaction regression and F-test for model fit were used to explore research observations and statistical verification of findings. The findings of this research is FWA is negatively related with WFC {B= -0.408, t (2.311) =-5.07, p
Keywords: Employment Nature; Flexible Work Arrangements; Flexible Policies; Job Status and Work-Family-Conflict.